Non-Canonical Notch Signaling Drives Activation and Differentiation of Peripheral CD4+ T Cells - Dongre, Anushka; Surampudi, Lalitha; Lawlor, Rebecca G.; Fauq, Abdul H.; Miele, Lucio; Golde, Todd E.; Minter, Lisa M.; Osborne, Barbara A. (Frontiers in Immunology, 2014)
Cleavage of the Notch receptor via a γ-secretase, results in the release of the active intra-cellular domain of Notch that migrates to the nucleus and interacts with RBP-JΚ, resulting in the activation of downstream target genes. This canonical Notch signaling pathway has been documented to influence T-cell development and function. However, the mechanistic details underlying this process remain obscure. In addition to RBP-JΚ, the intra-cellular domain of Notch also interacts with other proteins in the cytoplasm and nucleus, giving rise to the possibility of a alternate, RBP-JΚ independent Notch pathways. However, the contribution of such RBP-JΚ independent, “non-canonical” Notch signaling in regulating peripheral T-cell responses is unknown. In this report we specifically demonstrate the requirement of Notch1 for regulating signal strength and signaling events distal to the T-cell receptor in peripheral CD4+ T cells. By using mice with a conditional deletion in Notch1 or RBP-JΚ, we show that Notch1 regulates activation and proliferation of CD4+ T cells independently of RBP-JΚ. Furthermore, differentiation to TH1 and iTreg lineages although Notch dependent, is RBP-JΚ independent. Our striking observations demonstrate that many of the cell intrinsic functions of Notch occur independently of RBP-JΚ.. Such non-canonical regulation of these processes likely occurs through NF-ΚB. This reveals a previously unknown, novel role of non-canonical Notch signaling in regulating peripheral T-cell responses.